ANALISIS IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DI SEKOLAH DASAR NEGERI KABUPATEN GORONTALO - Witnansih Rahmatya Tanaiyo; Irvin Novita Arifin; Rifda Mardian Arif; Nurfadliah; Reska Putri Ismail (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The issue examined in this study is "how is the implementation of the pancasila student profile strengthening project carried out in state elementary schools in Gorontalo Regency?". The objective of this study is to describe the implementation of the pancasila student profile strengthening project in state elementary schools in Gorontalo Regency. This research employed a qualitative method, with observation and interviews as the data collection techniques. The data analysis technique used was qualitative analysis. The results of the study show that the implementation of the pancasila student profile strengthening project in state elementary schools in Gorontalo Regency has been carried out effectively. This is evident from the planning, implementation, achievement outcomes, evaluation, and follow-up stages of the project. Therefore, it is recommended that it order to achieve optimal results, the implementation of the pancasila student profile strengthening project must be supported by strong collaboration and cooperation between school principal, teachers, parents students, the Department of Education, and the wider Community.